A SNAPSHOT OF TYPE 1 DIABETES CARE AMONG ADULTS IN MALAYSIA: DATA FROM A SINGLE ACADEMIC MEDICAL CENTRE - Lim, Quan Hziung; Nazeri, Hannan Nazira; See, Caelyn Qi Ern; Ibrahim, Luqman; Khoo, Jun Kit; Ooi, Ying Guat; Sarvanandan, Tharsini; Hee, Nicholas Ken Yoong; Paramasivam, Sharmila Sunita; Ratnasingam, Jeyakantha; et al. (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND There is a dearth of data on adults living with Type 1 Diabetes (T1D) in Malaysia. METHODOLOGY This descriptive study aims to systematically collect current data and identify gaps among adults living with T1D in Malaysia. Data was extracted from electronic medical records of patients registered under the T1D clinic at Universiti Malaya Medical Centre (UMMC). All patients aged 18 and above in 2023 were included. RESULT There was a total of 107 patients with T1D (mean age 42.0 ± 12.7, mean HbA1c 8.0 ± 1.6%, mean BMI 24.5 ± 4.1 kg/ m2 ). The majority were Chinese (52.3%), followed by Malays (24.3%) and Indians (23.4%). The median age at T1D diagnosis was 18.0 years (IQR: 14.0). Almost half (42.1%) presented with diabetic ketoacidosis (DKA) at diagnosis. One in four patients had diabetes-associated autoantibody tests done. Autoantibody positivity was in this order: GADA (22.4%), ICA (6.5%), IA2A (5.6%) and IAA (1.9%). Co-morbid autoimmune conditions were reported in 16.2%, of which thyroid disease (61.1%) was most common. In terms of treatment, the majority were on analogue insulin (89.7%) delivered using multiple daily injections (79.4%). Of the 22 (20.6%) patients using insulin pumps, 50% were using manual pumps, whereas the others were using either sensor-augmented pumps or advanced hybrid closed-loop systems. Most (81.3%) patients used self-monitoring of blood glucose (SMBG) whereas 23.4% employed continuous glucose monitoring (CGM) systems for glycemic surveillance. Incident hypoglycemia within the preceding three months was reported among 60.7%, the majority (95.4%) of which were mild, and none reported severe. The incidence of DKA within the preceding six months was 4.7%. Retinopathy (19.6%) was the most prevalent complication, followed by kidney disease (15%) and atherosclerotic cardiovascular disease (7.5%). CONCLUSION This data serves as a baseline for a registry of local T1D patients, whereby future longitudinal analyses may unveil patterns of disease outcomes to guide clinical care unique to our setting.